Khinis/Bavian: Changing Models for an Assyrian Monumental Complex - Fales, Frederick Mario (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
There is no sculptural complex in the entire Assyrian empire as majestic as the one executed by Sennacherib (704-681 BC) in the rocky cliffs of Khinis/Bavian, although its overall monumental and conceptual logic is still open to discussion, as this overview – meant to blend in past reports and present-day critical approaches stretching over 170 years – will attempt to show. On the other hand, there never was any uncertainty regarding the extraordinary natural setting chosen for this display of imperial prowess, as this first quote reveals.